Money supply, inflation and output: An empirically comparative analysis for Vietnam and China - Pham Dinh Long; Bui Quang Hien; Pham Thi Bich Ngoc (Asian Journal of Economics and Banking (AJEB), 2024)
Purpose - This study focuses on analyzing the relation between money supply, inflation and output in Vietnam and China. Design/methodology/approach - Using the error correction model and the vector autoregression model (ECM and VAR) and the canonical cointegration regression (CCR), the study shows similar patterns of these variable relations between the two economies. Findings - The study points out the difference in the estimated coefficients between the two countries with different economic scales. While inflation in Vietnam is strongly influenced by expected inflation and output growth, inflation in China is strongly influenced by money supply growth and output growth. Originality/value - To the best of the authors' knowledge, this is the first empirical and comparative research on the relation between money supply, inflation and output for Vietnam and China. The study demonstrates that the relationship between money supply, inflation and output is still true in case of transition economies.
Keywords: E3; E45; O11; 330; Inflation; Monetary policy; Money supply; Output